Semi-analytical performance analysis of an SCM-WDM PON in the presence of XPM and GVD - Abdul Rashid, Hairul Azhar; Abbou, F. M.; Al-Qdah, Malik T.; Chuah, Hean Teik; Tayahi, M. B. (IEEE, 2007)
The authors analyze semi-analytically the performance in an SCM-WDM passive optical network (PON) in the presence of cross phase modulation (XPM) and Group Velocity Dispersion (GVD). A general expression for electrical average noise power and electrical crosstalk level due to XPM and GVD was derived to measure the system performance for N number of WDM channels. Using the expression, we show that XPM and GVD causes crosstalk in the system and imposes a power penalty as the number of WDM channels increases for a given channel spacing and modulating frequency.